The global response to the COVID-19 pandemic: how have immunology societies contributed? - Osier, Faith; Ting, Jenny P. Y.; Fraser, John; Lambrecht, Bart N.; Romano, Marta; Gazzinelli, Ricardo T.; Bortoluci, Karina R.; Zamboni, Dario S.; Akbar, Arne N.; Evans, Jennie; Brown, Doug E.; Patel, Kamala D.; et al. (Nature reviews. Immunology, 2020)
The COVID-19 pandemic is shining a spotlight on the field of immunology like never before. To appreciate the diverse ways in which immunologists have contributed, Nature Reviews Immunology invited the president of the International Union of Immunological Societies and the presidents of 15 other national immunology societies to discuss how they and their members responded following the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).
Gesehen am 20.10.2025